Perhitungan Biaya Produksi Alat Muat dan Angkut di Pit Mudak PT Teknik Alum Service: Calculation Of Production Cost Of Loading And Hauling Equipment At Mudak Pit Of PT Teknik Alum Service - Lantapi, Adriansyah Wuriadin Lantapi; Audina P Alhabsyi, Gina; Bundang, Syarifullah; Pakombong, Vhalentio; Winarno (CV Insight Publisher, 2025)
PT Teknik Alum Service is a company that mines nickel ore located in Buleleng.Village, Bungku Pesisir District, Morowali Regency, Central Sulawesi Province. The costs of loading and transporting nickel from the mine to the jetty using loading and transportation equipment are carried out to determine the components of production operating costs. Production costs are costs incurred during the production process. To produce large tool productivity for the company, of course, it is necessary to calculate the production costs of using the tool based on the production target plan that has been determined by the company. From this identification, the objectives of this research are asFollows: a. find out how much loading and conveyance equipment is produced at the Mudak Pit, b. Find out how much the production costs of loading equipment and conveyance are profitable for the company. PT Teknik Alum Service Teknik Alum Service has a monthly production target of 50,000 tons/month.